Exploration of correlation between slaughter value and data determined by X-ray computer tomography for Hungarian Simmental cattle - Holló, Gabriella; Egri, Edit; Repa, Imre; Holló, István (Animal welfare, Ethology and Housing Systems (AWETH), 2009)
In this study the determination of the relationship between the tissue composition of rib samples taken from the 11-13th ribs determined by X-ray computer tomography examination and the sub traits of slaughter value of Hungarian Simmental young bulls were aimed. In total, 30 Hungarian Simmental bulls were reared to 300.07 ± 43.78 kg initial live weight and 274.57 ± 19.73 d of age. Animals were distributed into three feeding groups with different maize silage to concentrate ratios (670:330 = Control; 750:250 = A group; 800:200 = B group) based on DM. The low concentrate groups (A and B) received linseed supplemented concentrate during the fattening period. According to our results the diet (forage to concentrate ratio, linseed supplementation) did not influence significantly the slaughter and dressing data as well as the tissue proportion determined by CT-examination. The mean area and muscle tissue area of longissimus were the highest on scans at 12th rib, whereas the fat area was on scans made at 11th rib. High correlations were presented between the meat, bone and fat content of carcass in relation to the muscle, bone and fat percentage of rib samples in order the correlation coefficients (r) were r = 0.88, r = 0.71 and r = 0.93. The EUROP meatiness classes show any relation to parameters measured by CT-examination. However, the EUROP fatness appeared controversial but significant relationship with CT-fat and muscle of both rib samples and longissimus muscle. Low and intermediate relationships (r = 0.37–0.69) were investigated between slaughter weight, weight of carcass, the dressing percentage and the muscle tissue of rib samples determined by CT. The dressing percentage presented with muscle tissue of longissimus a weak, positive relationship (r = 0.37–0.39). The four feet weight and the kidney fat proportion correlated with CT-bone (r = 0.57) and CT-fat of rib samples (r=0.79). Findings confirmed in line with previous results the reliable assessment of meat and fat of carcass with the usage CT-examination in case of the different feeding, too.
Keywords: cattle; slaughter value; X-ray computer tomography